Impact of exterior envelope thermal performance on energy demand and optimization strategies for university teaching-office buildings - Zu-An Liu; Yan Li; Jiawen Hou; Lei Tian; Shengcheng Wang; Wentao Hu; Lili Zhang (Scientific Reports)
Abstract It is very different from that of ordinary buildings due to the unique operational characteristics of university teaching-office buildings, and the energy-saving potential is huge, among them, the building’s exterior envelope is an important factor in its energy loss. It is an important basis for building energy conservation to explore the influence of the thermal parameter of the building exterior envelope on energy consumption from the perspective of thermal theory. Meanwhile, most of the buildings are old in university, limited by the actual conditions, studying the energy-saving optimization scheme from the main influencing factors and actual characteristics is a prerequisite for achieving high efficiency and energy saving. Therefore, based on the actual characteristics of university buildings, the influence law of the thermal performance of the exterior envelopes on energy demands is explored in this study through numerical simulation, and an energy-saving optimization scheme is proposed based on the existing materials. The results show that: (1) For university buildings in Chengdu, the energy-saving effect of the interior thermal insulation in exterior wall is the best; (2) the effect of insulation material type on total annual load tends to be the same as the insulation thickness is increased and stabilizes after the energy savings rate reaches 20%; (3) the selection of facing materials with low solar radiation absorption coefficients for exterior wall and roof has a much higher impact on cooling loads than on heating loads; (4) the suitable range of the heat transfer coefficient of the exterior window is 2.5 ~ 3.5, and the solar heat gain coefficient is 0.1 ~ 0.5; (5) using the optimization scheme can be saved by 18% of the heating load, 33% of the cooling load, and 28% of the total load compared to the status quo. The research results can provide a theoretical basis and data reference for energy-saving renovation of educational buildings.